Development of robust control law for active buffeting load alleviation of smart fin structures. (May 2014) - Chen, Yong; Ulker, Fatma D; Wickramasinghe, Viresh; Zimcik, David G
Aerodynamic buffeting load can lead to premature fatigue damage of aircraft vertical fin structures. This article presents a robust control law development strategy for active buffeting load alleviation of a smart fin structure. The impact of aerodynamic loads on the modeling uncertainties of the smart fin was investigated through extensive wind tunnel tests. Test results revealed that the airflow introduced higher damping ratio and caused frequency shift to the vibration modes. These aerodynamic effects may adversely affect the performance and robustness of active control laws. Based on the observations, the structured singular value synthesis technique was used to develop a robust control law for the smart fin using a truncated baseline dynamic model. A parametric uncertainty block was introduced to account for the changes in the modal parameters of the baseline dynamic model due to the aerodynamic effects. An additive uncertainty block was included to account for the unmodeled higher-order vibration modes as well as the modeling errors in the low frequency range. The robust performance of the control law was demonstrated through simulations as well as extensive closed-loop control experiments in the wind tunnel using various free airstreams and vortical airflows. This provided a verified control law design strategy for active buffeting alleviation applications.